Last night I had / the strangest dream / I ever dreamed before / I dreamed the world / had all agreed / to put an end to war - Donner, Ariadne (Information Centre of the World Peace Council)
Image of a child's face, made out from repetition of white doves and world maps Printed in Finnreklama Oy PO-1476